(untitled) (CAHIERS MAGELLANES-NS, 2024)
The article presents scientific information on the ecological and epizootological characteristics of domestic chicken helminthiases in North-Eastern Uzbekistan, as well as the diseases of raetiniosis, echinoleposis and choanotheniosis of domestic chickens, guinea fowl and turkeys.